Goat seropositivity as an indicator of Rift Valley fever (RVF) infection in human populations: A case-control study of the 2018 Rift Valley fever outbreak in Wajir County, Kenya - Omani, Ruth; Cavalerie, Lisa; Daud, A.; Cook, Elizabeth A.J.; Nakadio, Erenius; Fèvre, Eric M.; Gitao, G.; Robinson, J.; Nanyingi, M.; Baylis, M.; Kimeli, P.; Onono, J. (Elsevier, 2024)
Rift Valley fever (RVF) is a viral zoonosis, which is considered as a threat to food security in the Horn of Africa. In Kenya, RVF is the 5th ranked priority zoonotic disease due to its high morbidity and mortality, frequent outbreak events, and associated socioeconomic impacts during outbreak events. In 2018, an RVF outbreak was confirmed in Kenya's Siaya, Wajir, and Marsabit counties. During this outbreak, 30 people were confirmed infected with RVF through laboratory tests; 21 in Wajir, 8 in Marsabit, and 1 in Siaya Counties. Seventy-five (75) households (15 cases and 60 controls) were selected and interviewed using a case-control study design in 2021 (?). A case was a household with a member who was diagnosed with RVF in 2018. In addition, a total of 1029 animals were purposively selected within these households and serologically tested for RVF. The study aimed to estimate the contribution of various risk factors to RVF human occurrence in Kenya with a special focus on Wajir County. Wajir County was chosen due to high number of confirmed human cases reported in the 2018 outbreak. A univariable regression model revealed that owner-reported RVF virus exposure in livestock significantly increased the odds of an RVF human case in the household by 32.7 times (95 % CI 4.0–267.4). The respondent being linked to a goat flock that was IgG-positive increased the odds of an RVF human case by 3.8 times (95 % CI 1.17–12.3). In the final multivariable analysis, the respondent being linked to their own animals affected by RVF increased odds of having an RVF human case in the household by 56.9 times (95 % CI 4.6–700.4), while the respondent being linked to a neighbor household member affected decreased odds of having a RVF human case by 0.1 times (95 % CI 0.08–0.75). In summary, these results have revealed a potential link for the spread of RVF infection from animals to humans in pastoralist households, hence it is critical to carry out targeted, community education, One Health surveillance, prevention, and control measures against the disease. This will be critical to protecting humans against potential spillovers of infections during outbreak events in livestock.